Anguelovsky, Isabelle (2014). Neighborhood as refuge: Community reconstruction, place remaking, and environmental justice in the city - Anna Ortiz Guitart (Documents d'Anàlisi Geogràfica, 2016)
Anguelovsky, Isabelle (2014) Neighborhood as refuge: Community reconstruction, place remaking, and environmental justice in the city Cambridge: The MIT Press, 276 p. ISBN 978-0-262-52569-5